Shame, guilt and psychopathology - transdiagnostic approach - Adamczyk, Artur Olaf (Journal of Education, Health and Sport, 2017)
Shame and guilt belong together to the self-conscious emotions, but they have different effects on human psychological well-being. The work aims to present a systematic review of knowleadge on the subject and to present conclusions suggesting the potential transdiagnostic properties of shame in relation to various psychiatric disorders present in diagnostic manuals.